Prosedur dan Prinsip Dalam Penetapan Hadis Mansūkh - Lujeng Lutfiyah (ALAMTARA: Jurnal Komunikasi dan Penyiaran Islam, 2019)
As a reference in Islam, the Hadith structurally occupies the second position after the Qur'an. This is because the Qur'an is the word of God, while the hadith is the words of the Prophet. But in practice, both must be practiced together, because the hadith has an important function of the Qur'an, namely as a confirmation and explanation of Allah's statements in His book, as well as making rules or decrees that are not determined by Allah in the Qur'an. There are some verses that cannot be understood without going through the explanation of the hadith. With this important function, the study of hadith must continue to be developed, so that it remains an applicable guide throughout the ages.